Fe‐Doped Porous g‐C3N4: An Efficient Electrocatalyst with Fe‐N Active Sites for Electrocatalytic Hydrogen Evolution Reaction under Alkaline Conditions. Issue 21 (2nd June 2022) - Wang, Hefang; Sun, Peidong; Jiang, Hui; Li, Xiaobao; Ma, Xiaofei; Shao, Kai; Wang, Cui
Abstract: Herein, Fe‐C3 N4 ‐TU was prepared by one‐step pyrolysis of melamine (MA, carbon and nitrogen sources of g‐C3 N4 ) and Fe(NO3 )3 ⋅ 9H2 O using thiourea (TU) as a pore‐forming agent. Fe‐C3 N4 ‐TU exhibits a low Tafel slope of 82 mV ⋅ dec −1 and a low overpotential of 206 mV at the current density of 10 mA ⋅ cm −2 . The good HER (Electrocatalytic hydrogen evolution reaction) catalytic performance of Fe‐C3 N4 ‐TU is attributed to the high intrinsic activity of Fe−N(III) coordination structure and porous structure with the intersecting channels. The Fe−N(III) coordination structure is proved by the characterized results of the XRD, XPS, and FTIR, which originates from the strong affinity of rich pyridine N in the g‐C3 N4 to Fe ions. Simultaneously, the addition of TU as a pore‐forming agent induces the formation of large specific surface area and mesoporous structures with large pore diameters, which facilitate the exposure of Fe−N bonds and promotes H adsorption in the HER process. Abstract : Fe‐C3 N4 ‐TU was prepared by one‐step pyrolysis of Melamine (MA) and Fe(NO3 )3 ⋅ 9H2 O using thiourea (TU) as a pore‐forming agent. Fe‐C3 N4 ‐TU shows good catalytic activity under alkaline conditions, which is attributed to the high intrinsic activity of Fe−N(III) coordination structure and porous structure with the intersecting channels.